Progressive Muscle Relaxation in Managing Anxiety During Third-Trimester Pregnancy in the Banabungi Community Health Center Area: A Case Study - Sri Resky Mustafa; Wildayani; Muhaimin Saranani (Kiara Group, 2026)
Background: Anxiety during the third trimester of pregnancy, if left unmanaged, can adversely affect both maternal and fetal outcomes. Elevated anxiety levels may prolong labor due to increased uterine muscle tension and stress hormone secretion, leading to ineffective contractions. Moreover, maternal anxiety is associated with fatigue, sleep disturbances, infection, preterm birth, low birth weight, prolonged labor, and impaired mental and motor development in children. Progressive Muscle Relaxation (PMR) is a non-pharmacological intervention that may help reduce muscle tension and psychological stress during pregnancy. Objective: This study aimed to examine the implementation of Progressive Muscle Relaxation exercises over a three-day period and their effect on anxiety levels in a third-trimester pregnant woman in Kombeli Village. Methods: A descriptive case study with a pre–post test design was conducted. The subject was Mrs. R, a 27-year-old woman in her third trimester of pregnancy, observed from May 29 to May 31, 2025. Progressive Muscle Relaxation exercises were administered once daily for 5–10 minutes. Anxiety levels were assessed using the Pregnancy-Related Anxiety Questionnaire–Revised 2 (PRAQ-R2), categorized as mild (<23), moderate (23–37), and severe (>37). Results: Following the intervention, the anxiety score decreased from 39 (severe anxiety) to 33 (moderate anxiety). Conclusion: Progressive Muscle Relaxation exercises contributed to a reduction in anxiety levels in a third-trimester pregnant woman. Although the decrease was not substantial, PMR demonstrated potential as a supportive non-pharmacological intervention for anxiety management during pregnancy.